Proximate composition, fatty acid characteristics, and amino acid profile of European anchovy (Engraulis encrasicolus L. 1758): monthly and seasonal influences - Karslı, Barış; Öğretmen, Özen Yusuf; Emanet, Muhammet (Frontiers in Nutrition, 2025)
This study investigated the proximate composition, amino acid, and fatty acid profiles of anchovy (Engraulis encrasicolus) collected from the Southeastern Black Sea on both monthly and seasonal bases. Crude protein (17.65–20.24%), crude fat (5.29–14.51%), moisture (64.61–73.12%), and crude ash (1.30–1.82%) contents showed significant fluctuations. Palmitic acid was the dominant saturated fatty acid (16.97–20.89%). Polyunsaturated fatty acids (PUFAs) reached their highest values in summer (33.50%) and June (35.30%), while the lowest levels were detected in autumn (28.76%) and November (27.14%). Eicosapentaenoic acid (EPA) peaked in spring and May (up to 8.95%) and was lowest in autumn and September (6.47%). Docosahexaenoic acid (DHA) was highest in summer and September (19.86%) and lowest in autumn and November (13.78%). The atherogenicity and thrombogenicity indices varied between 0.77–0.73 and 0.81–0.69 seasonally, and 0.35–0.90 and 0.36–0.27 monthly, respectively. Total essential amino acids ranged from 8,727 to 10,039 mg/100 g, while total non-essential amino acids ranged from 7,961 to 8,894 mg/100 g. Lysine was the most abundant essential amino acid, whereas glutamic acid was the predominant non-essential amino acid.